The Screening, Awareness, Treatment, and Control of Dyslipidemia Among Adults in Ulaanbaatar, Mongolia - Unurjargal, Tsolmon; Myagmardorj, Rinchyenkhand; Sukhbaatar, Amarjargal; Badrakh, Burmaa; Byambatsogt, Bolortuul; Erdenedagva, Oyunsuren; Bayartsogt, Batzorig; Vanchin, Byambasuren (Central Asian Journal of Medical Sciences, 2019)
Objective: The prevalence of dyslipidemia continues to increase in recent decades in Mongolia; however, little is known about awareness, treatment, and control of dyslipidemia. The aim of this study was to assess the awareness, treatment, and control of dyslipidemia in adults in Ulaanbaatar, Mongolia. Methods: This cross-sectional study was conducted between June 2017 and March 2018. A total of 326 people in Ulaanbaatar participated in this study. Results: Out of the 326 participants, 224 (68.7%, 64.9 in females; 75% in males) had dyslipidemia, and around the one third 113 (34,7%) were aware of the condition. Out of the 224 dyslipidemia individuals, only 27 (8.3%) were on statin treatment. Among those individuals receiving treatment, 19 (70.4%) serum lipid level was under the desired level. Conclusion: Our study revealed an alarmingly high prevalence of dyslipidemia, low level of awareness, insufficient treatment, yet a comparatively high level of control of dyslipidemia among the adults aged 20- 69 in Ulaanbaatar relative to some other countries. The awareness, treatment, and control of dyslipidemia in the rural parts of Mongolia are unknown.